EXPERIMENTAL METHOD TO INCREASE SCIENCE PROCESS SKILLS MATERIALS FOR CHANGING OBJECTS CLASS V SDS PLUS AL MUBAROKAH - Rosi Maulidya Ardhana; Agung Setyawan (Citra Dharma Cindekia, 2022)
This study aims to improve science process skills in science learning the material of changing the shape of objects in fifth grade students of SDS Plus Al Mubarokah through the experimental method. This type of research is collaborative classroom action research with the research design of the Kemmis & McTaggart model consisting of 4 stages including planning, action, observation, and reflection. The subjects of this research were 4 students of class V. This research was conducted in 2 cycles, each cycle consisting of 2 meetings conducted by applying the experimental method. The technique of collecting data in this research is through interviews, observation, documentation, and worksheets. Data collection instruments in the form of interview sheets, observation sheets, documentation sheets, and worksheets. In this study, the data analysis technique used was descriptive qualitative and quantitative data analysis. The results of this study indicate that the application of the experimental method can improve students' science process skills by 25%. The average score of students' science process skills in the first cycle was 62.5% and in the second cycle it was 87.5%. In conclusion, the application of the experimental method can improve the science process skills of the fifth grade (Five) SDS Plus Al Mubarokah students in learning the science of changing the shape of objects.